Safety and Efficacy of Fremanezumab for the Prevention of Migraine: A Meta-Analysis From Randomized Controlled Trials - Gao, Bixi; Sun, Nan; Yang, Yanbo; Sun, Yue; Chen, Mingjia; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2020)
Background Fremanezumab (TEV-48125) is a fully-humanized immunoglobulin G isotype 2a selective monoclonal antibody that potently binds to calcitonin gene-related peptide (CGRP). It is one of the novel therapeutic drugs for the prevention of migraine, which is one of the most common neurological diseases worldwide. Several controlled trials have been conducted to investigate the safety and efficacy of fremanezumab, however, there is no systematic review of the existing literature has been performed. Hence, in our study, we performed a meta-analysis to investigate the safety and efficacy of fremanezumab for the prevention of migraine. Method Pubmed (MEDLINE), Embase, and Cochrane Library were searched from January 2001 to August 2019 for randomized controlled trials (RCTs). Five RCTs with 3379 patients were finally included in our study. Result We pooled 3379 patients from 5 RCTs; the primary endpoints were mean monthly migraine and headache days, baseline to week 12. We found that fremanezumab led to a significant reduction in migraine days (P < 0.0001) and headache days (P < 0.0001) during 12 weeks compared with placebo. Moreover, after using fremanezumab, the risk of at least one adverse event (AE) (P=0.001) and AE related to the trial regimen (P=0.0005) significantly increased compared with the placebo. Conclusions Fremanezumab showed good efficacy for the prevention of migraine. The administration of fremanezumab can cause some mild adverse events but no serious adverse events.